Osteomyelitis: A Literature Review - Rawung, Rangga; Moningkey, Chita (Jurnal Biomedik : JBM, 2019)
Abstrak: Infeksi pada tulang dan sendi masih merupakan kasus yang menantang. Kondisi ini memberikan banyak penyulit baik kepada dokter maupun pasien. Meski terapi antibiotika dilaporkan memberikan hasil yang memuaskan pada banyak kasus infeksi, tidak demikian pada kasus infeksi tulang dan sendi. Hal ini berhubungan dengan struktur anatomi dan fisiologi dari tulang. Diperlukan sebuah strategi tata laksana yang baik untuk mencapai hasil yang optimal. Prinsip dasar yang utama dalam mencapai pengobatan yang optimal ialah penegakan diagnosis awal yang tepat, termasuk di dalamnya proses investigasi pemeriksaan mikrobiologi dan patologi. Diperlukan pengertian dasar serta pengenalan kembali anatomi, fisiologi, patofisiologi, dan tata laksana terkini tentang osteomielitis untuk mencapai tatalaksana yang optimal.Kata kunci: diagnosis dan tata laksana osteomielitisAbstract: Infection in bone and joint is still a challenging case. It gives a lot of problems and frustration to the physician and patient. The successful antibiotic therapy in most infectious diseases is abortive to achieve in bone and joint infections because the different characteristic in anatomy and physiology of these structures. Therefore, treatment strategy, including non operative and operative techniques is required to deal with such conditions. The basic principle to achieve a successful management of osteomyelitis in general is correct initial diagnosis including investigation for microbiological and pathological examinations to allow the proper and long term lasting therapy of antibiotic. For that reason, it is required to have the basic understanding in dealing with this issue, obvious and updated. It is commited to review the pathophysiology, the diagnosis, and the management of osteomyelitis in order to presents basic facilities in dealing with osteomyelitis.Keywords: osteomyelitis diagnosis and management